A cooling off period: decline in the use of hot biopsy forceps technique in colonoscopy in the U.S. Medicare population 2000–2019 - Andrew J. Read; Jacob E. Kurlander; Akbar K. Waljee; Sameer D. Saini (BMC Gastroenterology)
Abstract Background The use of hot biopsy forceps (with electrocautery) is no longer routinely recommended given increased complications compared to cold biopsy forceps (without electrocautery). It is unknown how often the technique is currently used in the United States (U.S.) or how its usage has changed over time. Aim To characterize the use of hot biopsy forceps by U.S. Medicare providers over time, identify provider characteristics of those who more commonly perform this technique, and determine if there are regional differences in use of this technique within the U.S. Methods We performed a retrospective cross-sectional study using U.S. Medicare summary data from 2000 to 2019 to analyze the frequency of cold and hot biopsies. We used detailed provider and state summary files to characterize providers’ demographics, including geographic region, to identify regional variation in use of these techniques, and identify factors associated with use of hot biopsy forceps from 2012 to 2019. Results The hot biopsy forceps technique peaked in 2003 (412,165/year) and declined to 108,232/year in 2019, while the cold biopsy forceps technique increased from 482,862/year in 2000 to 1,533,558/year in 2019. Use of hot biopsy forceps was more common by non-gastroenterologists and in rural practice settings. In addition, there was up to 50-fold difference in utilization in these techniques between states (on a population normalized basis), with the highest rate of use in the southeastern U.S. Conclusion Variation in the use of hot biopsy forceps by region and provider suggests a potential area for quality improvement given the comparative advantages of the cold biopsy forceps technique. De-implementation of an existing endoscopic practice may require different approaches than implementation of a new practice.